PENGARUH SISTEM PENGENDALIAN INTERN PEMERINTAH, IMPLEMENTASI STANDAR AKUNTANSI PEMERINTAHAN, PENYELESAIAN TEMUAN AUDIT TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH DAN IMPLIKASINYA TERHADAP PENERAPAN PRINSIP-PRINSIP TATA KELOLA PEMERINTAHAN - Diana Sari (Indonesian Journal of Economics and Business, 2012)
The governmental obligation to promote the public interest through the implementation Good Government Governance or in other word a central issue presented by the government assuring that the government through her civil servants to represent and respond the interest of the citizenry. But there are many aspect of the civil servant that make it difficult to attain satisfactory level of Good Government Governance that could be proved by results of BPK RI audit on  local government financial statement. This fact finding must be improved continuously.The research was aim to test and to analyze the influence of the government internal control system, the implementation of government accounting standards, the completion of the audit findings on the quality of local financial statements and its implications on Good Government Governance principles. The research was an explanatory research. The respondent of the research was a local government consist of Regional Governments, regencies and cities in West Java and Banten Province. The data was collected using questionnaire and interview technique follow by using descriptive analysis and path analysis.            The result of the research show that: (1) government internal control system, the implementation of government accounting standard, and completion of the audit findings have positive influences towards the quality of local government financial statements; (2) government internal control system, the implementation of government accounting standards, completion of the audit findings and the quality of local government financial statements have positive influences on implementation of the Good Government Governance.